Mauritius : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
The Mauritian economy showed strong performance owing to its sound macroeconomic policies. Executive Directors emphasized the need to remain competitive and address the growing unemployment problem. They commended the efforts to support the developments in financial services, free port activities, and information and communications technology. They appreciated the tightening of the monetary policy and stressed the need to strengthen the financial position and ensure fiscal sustainability. They welcomed the assessment of the effectiveness and efficiency of the IMF, which provided technical assistance to Mauritius.